PENGARUH LAYANAN INFORMASI PEMANFAATAN WAKTU LUANG TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS VIII B SMP NEGERI 1 SINDUE TOBATA - Yusna, Yusna; Thalib, Mansyur; Syahran, Ridwan (Jurnal Konseling dan Psikoedukasi, 2017)
The problem in this research is how learning independence of students before and after implementation of information service utilization of leisure time, also is there learning independence of students after implementation of information service utilization of leisure time higher than before given the information services utilization of leisure time. This research intented to describe and explain the improvement of learning independence students before and after implementation of information service utilization of leisure time. The subjects in this research were 20 students. The instrument was collected by having learning independence questionnaire.Â  The data was processed and analyzed in descriptive and inferentially using the formula t-test (one-tailed) in 95% significance level. The result of descriptive analysis showed that before implementation of information service there were 20% of students had high learning independence, 70% of students had low learning independence, and 10% of students had very low learning independence. On the other side after implementation of information service there were 55% of students had high learning independence and 45% of students had low learning independence.Â  The result of inferential analysis showed the learning independence of students after implementation of information service utilization of leisure time higher than before given the information services utilization of leisure time.